Examining a developmentally based measure of L2 oral performances: Does it predict L2 learners' oral proficiency?. (April 2020) - Mostafa, Tamanna; Kim, YouJin; Friginal, Eric
Abstract: Although structural complexity of learners' oral production has often been correlated with proficiency, there has been less focus into whether high proficiency L2 learners use L2 forms that belong to higher levels in developmental sequences. The purpose of this study is to investigate whether an index based on the developmental levels of second language (L2) morphological and syntactic forms (Index of Developmental Levels, IDL) predict L2 oral proficiency and learners' institutional placement in different class-levels (beginner, intermediate, advanced) and whether IDL is a better predictor of these variables compared to widely-used structural complexity measures (mean length of AS-unit and subordination measure). The dataset included monologic oral presentations from English as second language (ESL) learners ( n  = 60) of varied proficiency levels. Each speech-sample was rated for oral proficiency by two expert raters using the TOEFL independent speaking rubric. The results showed IDL as a significant positive predictor of L2 oral proficiency scores and learners' placement in class-levels. IDL was also found to be a stronger predictor of learners' oral proficiency and institutional placement compared to subordination measure. The results are discussed with reference to the importance of including developmentally based measures for gaining informed insights into L2 oral performances.